PENGARUH DIGITAL LEADERSHIP, MEDIA SOCIAL, DAN DIGITAL TRANSFORMATION TERHADAP EMPLOYEE PERFORMANCE - Jessy Krisna Ineike; Tiara Puspa (EBID: Ekonomi Bisnis Digital, 2025)
This study aims to analyze the effect of Digital Leadership, Social Media, and Digital Transformation on Employee Performance in a government office environment. The research background is based on the need for organizations to adapt to the development of digital technology in order to improve efficiency and employee performance. This research uses a quantitative approach with a survey method through distributing questionnaires to 160 employees who work at the head office and representative offices. The data analysis technique used multiple linear regression with the help of SPSS software version 21. The results showed that Digital Leadership and Social Media have a positive and significant effect on Employee Performance. In contrast, Digital Transformation has a negative and insignificant effect on employee performance. This finding suggests that although digital transformation is important, its suboptimal implementation can actually hinder productivity. This research provides managerial implications that it is important for organizations to strengthen digital leadership and social media utilization, and conduct a thorough evaluation of digital transformation strategies in order to have a more positive impact on employee performance.